TEACHING STRATEGIES FOR READING COMPREHENSION: ADHD STUDENTS: กลวิธีการสอนอ่านเพื่อความเข้าใจสำหรับผู้เรียนสมาธิสั้น - Pothi, Parichart; Sriyabhaya, Warawat (Journal of Education and Innovation, 2020)
This article presents reading comprehension strategies for ADHD students including Reciprocal teaching and TWA teaching (Think Before Reading, Think While Reading, and Think After Reading). The article is for supporting Thai language teachers in point of the reading comprehension guidelines for learners of various styles, and also provides the teaching processes which encourage self-regulated learning of students based on the cooperative learning and analytical thinking. Furthermore, the proposed teaching strategies can support the development of reading comprehension skills for further learning in other courses and lifelong learning.